Hubungan Penerapan Australasian Triage Scale dengan Response Time Perawat di Instalasi Gawat Darurat - Aulia, Salshabilla Ramadhisa; Hidayah, Nurul; Purborini, Nurul (Borobudur Nursing Review, 2026)
Background: The Emergency Department (ED) is a vital hospital unit that provides prompt and accurate care for patients in critical condition. The Australasian Triage Scale (ATS) classifies patients according to the severity of their condition, and accurate implementation can reduce nurses’ response times and improve service quality. At the ED of Tidar regional public hospital Magelang, nurses’ understanding of ATS is generally good; however, its application is not always consistent. Objective: The objective of this study is to investigate the correlation between the implementation of the Australasian Triage Scale (ATS) and nurses response time at the Emergency Department of Tidar regional public hospital Magelang. Method: This quantitative study employed a correlational observational design. A total of 33 ED nurses were selected using total sampling. Data were collected through observation and questionnaires, analyzed descriptively using univariate analysis for respondent characteristics, and tested using the Lambda correlation in bivariate analysis. Results: Most respondents were aged 26–45 years (93.9%), male (75.8%), held a Diploma in Nursing (93.9%), and had more than two years of work experience (100%). The majority demonstrated accurate ATS implementation (87.9%), and most had very fast response times (60.6%). Bivariate analysis revealed a significant correlation between ATS implementation and nurses’ response time (p = 0.033; r = 0.471), indicating a moderate positive relationship. Conclusion: There is a significant positive correlation between accurate ATS implementation and faster nurse response times. Improved ATS application contributes to enhanced quality and patient safety in the Emergency Department.